2016
DOI: 10.1111/hsc.12338
|View full text |Cite
|
Sign up to set email alerts
|

Marginalisation, discrimination and the health of Latino immigrant day labourers in a central North Carolina community

Abstract: The morbidity and mortality of Latino immigrants in the United States (US) stem from a complex mix of policy, culture, discrimination, and economics. Immigrants working as day labourers may be particularly vulnerable to the negative influences of these social factors due to limited access to social, financial, and legal resources. We aimed to understand how the health of male Latino day labourers in North Carolina, US is influenced by their experiences interacting with their community and perceptions of their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
37
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 38 publications
(64 reference statements)
1
37
0
Order By: Relevance
“…This puts agricultural workers at disproportionate risk of being unable to secure care if they experience a work-related accident. We found no empirical research examining the impact of state E-Verify, minimum wage, overtime, and worker’s compensation provisions on immigrant or Latino health; however, research among Latino immigrants in North Carolina found that the discrimination and marginalization resulting from dangerous working conditions and unsteady employment affected men’s health and wellbeing (Fleming et al, 2016). In addition, poverty-focused research clearly demonstrates that income and material resources have a critical impact on health (Alaimo et al, 2001; Ettner, 1996) and other work has shown that workers’ compensation positively affects self-reported health among injured workers (Lippel, 2007).…”
Section: Resultsmentioning
confidence: 99%
“…This puts agricultural workers at disproportionate risk of being unable to secure care if they experience a work-related accident. We found no empirical research examining the impact of state E-Verify, minimum wage, overtime, and worker’s compensation provisions on immigrant or Latino health; however, research among Latino immigrants in North Carolina found that the discrimination and marginalization resulting from dangerous working conditions and unsteady employment affected men’s health and wellbeing (Fleming et al, 2016). In addition, poverty-focused research clearly demonstrates that income and material resources have a critical impact on health (Alaimo et al, 2001; Ettner, 1996) and other work has shown that workers’ compensation positively affects self-reported health among injured workers (Lippel, 2007).…”
Section: Resultsmentioning
confidence: 99%
“…Disparities in marginality among individuals partly explain differences in health and the quality of life among Americans (Havranek et al., ). For instance, evidence suggests that both the experience and the perception of marginalization are linked to poor health through stress, anxiety, depression, occupational injuries, and limited access to health care services (Fleming, Villa‐Torres, Taboada, Richards, & Barrington, ). Therefore, the reduction of health disparities to promote health equity requires researchers and clinicians to conceptualize patient vulnerabilities in the framework of their personal needs and daily realities.…”
Section: Implications For Practice and Future Researchmentioning
confidence: 99%
“…The potentially detrimental health effects of immigration-and enforcement-related omnibus laws on undocumented immigrants are exacerbated by policies related to labor and employment, education, and driver's licenses. Restricted access to labor markets and experiences with unjust and unfair working conditions have been shown to not only reduce material well-being but also to exacerbate feelings of exclusion and isolation [7]. Legislation that restricts access to education for undocumented immigrants may also have detrimental consequences for social and economic mobility, as well as deleterious long-term health effects, by hindering access to opportunities and resources that promote positive downstream health outcomes [8].…”
Section: Introductionmentioning
confidence: 99%